Rejeição aguda no transplante renal pediátrico: epidemiologia, fatores de risco e impacto sobre a função renal - Pereira, Luiza Do Nascimento Ghizoni [UNIFESP] (2019)
Objectives: To evaluate the incidence of acute rejection in pediatric patients submitted to kidney transplantation, as well as the related risk factors and impact of this outcome in allograft function and survival during follow up. Methods: Retrospective cohort including all pediatric patients submitted to kidney transplant between 2011 and 2015. The effects of possible risk factors for acute rejection were tested by Competing Risk Analysis. To estimate the impact of this outcome in allograft, we evaluated graft survival adjusted for acute rejection occurrence and variability in the glomerular filtration rate by Schwartz’s formula during the follow up. Results: The cohort included 230 patients, and rejection free survival rate was 72.5% in one year and 54.8% in five years. The risk factors to this outcome were number of mismatches (SHR 1.36 CI 1.14 – 1.63 p=0.001), immunosuppression based on cyclosporine, prednisone and azathioprine (SHR 2.22 CI 1.14 – 4.33 p=0.018), delayed graft function (SHR 2.49 CI 1.57-3.93 p<0.001), CMV infection (SHR 5.52 CI 2.77 – 11.0 p<0.001) and bad-adherence (SHR 2.28 CI 1.70 – 4.66 p<0.001). Death censored graft survival in one and five years were respectively 92.5% and 72.1%, and the risk factors for this outcome were number of mismatches (HR 1.51 CI 1.07 – 2.13 p=0.01), age over 12 years old (HR 2.66 CI 1.07 – 6.59 p=0.03) and panel reactive antibody between 1 and 50% (HR 2.67 CI 1.24 – 5.73 p=0.01). Despite the occurrence of acute rejection did not influence 5 years graft survival, it presented a negative impact on glomerular filtration rate. Conclusion: Acute rejection is a frequent outcome in our patients, being related to number of mismatches, immunosuppression with cyclosporine, prednisone and azathioprine, delayed graft function, CMV infection and bad adherence, and it has some impact in GFR during follow up.